Survey of Neurohospitalists: Subspecialty Definition and Practice Characteristics - Likosky, David; Shulman, Scott; Restrepo, Lucas; Freeman, William D. (Frontiers in Neurology, 2010)
Background: Neurohospitalists represent an emerging neurological subspecialty focusing on inpatient neurological disease. Little data exists regarding neurohospitalist practice information and clinical activity. A survey among neurohospitalists was performed to help define the subspecialty, yield demographic information, practice characteristics, and understand clinical and non-clinical activities. Methods: During the formation the Neurohospitalist Section of the American Academy of Neurology September 2008, an online survey (29 questions mixed categorical, numerical, and free text) of 93 neurohospitalists was performed. The survey closed on Oct 13th 2008. Results: The survey achieved a 54% response rate. 82% of respondents were male, mean age 42 (range, 34 to 68), median practice duration 6 years, with broad distribution of practices across the U.S. 75% of respondents reported having general neurology residency plus additional fellowship training (54% vascular neurology fellowship, 13% neurocritical care, and 33% other/no response). 51% of neurohospitalists were hired by non-academic (private) institutions, whereas academic institutions hired 49%. There was a wide array of responses for call frequency, duration, number of practice partners, and annual income. A uniform definition of the neurohospitalist subspecialty emerged as one who cares for inpatients, focusing primarily on in-hospital responsibilities. Conclusion: Neurohospitalists defined themselves as inpatient neurological subspecialists. Neurohospitalists have a broad U.S geographic distribution (and possibly international), in both academic and private practice (or hybrid) forms, and typically provide inpatient and Emergency Department call coverage for hospitals or outpatient neurologic practices. Most neurohospitalists were involved in administrative aspects of stroke or inpatient quality initiatives.